The role of perceived quality, store image, and trust in predicting customers' purchase intentions towards restaurants in Terengganu / Khalid Amin Mat ... [et al.] - Mat, Khalid Amin; Mohamad, Ahmad Abdullah; Omar Ali, Siti Rapidah; Mohd Said, Nur Shafini (Universiti Teknologi MARA, Perlis, 2020)
The restaurant industry is highly competitive and the entrepreneur must pay attention to customers' purchase intentions in order to have chances to stand out from the competitors. It is a crucial aspect for every entrepreneur to look deep into. Getting customers' intention is like a war in marketing arena to all business to maintain the restaurants survival. Choosing a restaurant comes almost automatically when one feels hungry and it does not need much information. There are characteristics behind every purchase decision that can come from extrinsic, intrinsic, and consumer attitude. Each of these factors includes dimensions that can be utilised in business strategy. Entrepreneurs can use these factors so delicate, so that customers might not even recognise it. Customers might think that they have always purchased the same brand or product but they do not realise that the affecting factors behind this decision can come from perceived quality, store image, and trust. This study focuses and contributes the knowledge about role of perceived quality, store image and trust that affect customers' purchase intentions. The purpose of this study is to investigate the relationship between perceived quality, store image and trust towards customers' purchase intentions. The study describes that the relation between independent variable have significant relationship with customers' purchase intentions. This is quantitative study with a sample size of 210 respondents. Researcher distributed 210 questionnaires to be used for data analysis. The results of this study show that perceived quality, store image and trust have significant relationship with customers' purchase intentions. Further research is required to cover other factors that can also affect the customers' purchase intentions and at the same time close the current gaps in our understanding of customers' purchase intentions as a whole.